The Relationship Between Mindfulness and Subjective Well-being in Employed Women: The Mediating Role of Assertiveness - Tayebi, Somayeh; Barzegar, Majid; Mohammadipour, Mohammad (Iranian Journal of Neurodevelopmental Disorders, 2025)
Article type: Original Research How to cite this article: Atri, R., Shafizadeh, H., & Soleimani, N. (2025). The Relationship Between Mindfulness and Subjective Well-being in Employed Women: The Mediating Role of Assertiveness. Iranian Journal of Neurodevelopmental Disorders, 4(1), 55-63. https://doi.org/10.61838/kman.jndd.4.1.7 © 2025 the authors. Published by Iranian Association for Intelligence and Talent Studies, Tehran, Iran. This is an open access article under the terms of the Creative Commons Attribution-NonCommercial 4.0 International (CC BY-NC 4.0) License. Purpose: The present study aimed to examine the mediating role of assertiveness in the relationship between mindfulness and subjective well-being among employed women. Methods and Materials: This descriptive-correlational study used structural equation modeling (SEM) to analyze data collected from a sample of 480 employed women working in governmental offices in Shiraz during the last six months of 2024. Participants were selected through convenience sampling. Three validated self-report instruments were used: the Five Facet Mindfulness Questionnaire (Baer et al., 2006), the Rathus Assertiveness Schedule (Rathus, 1973), and the Subjective Well-being Scale (Keyes & Magyar-Moe, 2003). Data were screened for multivariate normality, and model fit was assessed using AMOS software. Descriptive statistics, correlation analysis, and path analysis were employed to test the proposed mediation model. Findings: Results revealed that mindfulness had a significant direct effect on both assertiveness (β = 0.585, p < .001) and subjective well-being (β = 0.579, p < .001). Assertiveness also had a significant direct effect on subjective well-being (β = 0.299, p < .001). Additionally, the indirect effect of mindfulness on subjective well-being through assertiveness was statistically significant (β = 0.175, p < .001), with a total effect of β = 0.754. Fit indices confirmed the adequacy of the proposed model (χ²/df = 1.83, RMSEA = 0.055, CFI = 0.978). Conclusion: The findings suggest that assertiveness partially mediates the relationship between mindfulness and subjective well-being in employed women. Enhancing mindfulness may not only directly improve well-being but also indirectly increase it by fostering assertive behavior. These results highlight the importance of integrated psychological training in workplace mental health initiatives for women.